Microbial Flora Changes in Cesarean Section Uterus and Its Possible Correlation With Inflammation - Yang, Xing; Pan, Xinyi; Cai, Meihong; Zhang, Bolun; Liang, Xiaoyan; Liu, Guihua (Frontiers in Medicine, 2021)
Background: It has not been fully elucidated whether the change of the uterus flora is correlated to impaired fecundity. This case-control study aimed to analyze the differences in uterus microbial flora between women with post-cesarean section (CS) scar diverticulum (PCSD) (CS group) and women after vaginal delivery (control group), exploring the correlation between differentially expressed microbial flora and inflammation. Methods: Infertile women who underwent hysteroscopy were enrolled in this case-control study. The swab samples were classified into four subgroups: CS cervix group, CS endometrium group, control cervix group, and control endometrium group. The total DNA obtained from 16 women (a total of 31 samples, the cervix or endometrium) was extracted for 16S recombinant DNA (rDNA) analysis. The Luminex platform was used to detect the abundance of 34 kinds of local inflammatory cytokines in 32 endometrium samples, and the correlation between microbial flora and inflammatory cytokines was analyzed. Results: The alpha and beta diversity analysis indicated that the microbial diversity was higher in the CS group compared to the control group, especially in endometrium tissues. The heatmaps revealed that the microbial flora structure differs at each level of the phylum-class-order-family-genus among the groups. The analysis of four of the most prominently changed microbial flora revealed that Lactobacillus in the cervix was significantly higher in the control group when compared with the cesarean section group (P < 0.05). Furthermore, Proteobacteria and Neisseriaceae had a higher abundance in the CS groups, especially in the cervical tissue (P < 0.05), while Staphylococcaceae increased only in the CS endometrium tissue (P < 0.05). Next, these women were re-divided into the high- and low-Staphylococcaceae, and the abundance of 34 kinds of local inflammation cytokines was compared between groups. It was found that there was a positive correlation between Staphylococcaceae and IL-2, and a negative correlation between Staphylococcaceae and IL-8 (P < 0.05). Conclusion: The present results suggest that the disrupted uterus microbiota composition in women with CS may be closely associated with local inflammation. The interplay between the microbiota and the immune system may be linked to clinical disorders. The potential mechanisms require further exploration.